Markanvändningens förändring i vardagslandskapet - Israelsson, Jessica (2009)

(untitled)
During the last 100-200 years people have change their way of living and the condition and need for survival is no longer depending on the agricultural work. The forestry has replaced the farming and a lot of the natural pastural have been lost.